Proposal of novel degradation diagnosis method for photovoltaic module employing xenon flash lighting system and detector capacitor. (15th April 2019) - Tanaka, T.; Hayashi, T.; Nagayama, T.; Yanagidaira, T.; Inui, Y.
Highlights: A novel degradation diagnosis method for photovoltaic modules was proposed. The proposed method utilizes xenon flash lighting system and detector capacitor. The proposed method includes sensing process of module temperature. The proposed method can evaluate increase of module internal series resistance. The proposed method can find out modules with broken bypass diode. Abstract: This paper proposes a novel and unique degradation diagnosis method for photovoltaic modules employing a xenon flash lighting system and a capacitor for degradation detection connected to the module output. The xenon flash lighting system is not only compact and lightweight but also small in power consumption and can be lit by batteries. Therefore, the portability of the lighting system is satisfactory, and the proposed diagnosis method is expected to be relatively easily applicable to outdoor photovoltaic power plants. In addition, since the lighting system can provide artificial and precisely controlled intense flash light to the module and this proposed method includes a sensing process of the module temperature, this proposed method can, in principle, evaluate the internal series resistance and determine accurate degradation level independent of the weather and temperature conditions. The authors carried out the numerical simulations and successfully made clear that the theoretically unavoidable measurement error of the internal series resistance is only 2% less than its variation width, confirming the validity of the basic ideas of the proposed degradation diagnosis method. The authors then performed the demonstration test experiments using a prototype experimental apparatus and investigated its practicability for real PV modules, successfully confirming that the same accuracy as expected through the simulations can be achieved also through the experiments.